Discovery of Novel Alkaloids from Magnolia Genus: A Literature Review from 2002-2024 - Yuniarta, Tegar Achsendo; Handayani, Rosita (Borneo Journal of Pharmacy, 2025)
The genus Magnolia, encompassing hundreds of globally distributed species, has a long-standing history in traditional medicine for treating diverse ailments. These species are particularly renowned for their rich array of bioactive compounds, notably alkaloids. This study provides a comprehensive summary of novel alkaloid compounds identified in various Magnolia species within recent years. Through a targeted literature review utilizing Google Scholar and PubMed (2002–2024), we pinpointed nine novel alkaloids and one nitrogen-based compound isolated from four distinct Magnolia species. These newly discovered compounds exhibited promising bioactivities, including significant antiplatelet and anti-acetylcholinesterase effects. Structurally, the majority of these compounds belong to the aporphine and benzylisoquinoline classes, although some display unique configurations, such as glycosidic or N-oxide alkaloids. This review aims to bridge a critical gap in the existing scientific literature regarding the comprehensive documentation of novel alkaloid secondary metabolites found across the diverse Magnolia genus.